Docetaxel hydrate induces apoptosis and suppresses tumorigenesis of oral Burkitt’s lymphoma cells (in vitro and in vivo studies) - Supriatno, Supriatno (Padjadjaran Journal of Dentistry, 2019)
Introduction: Burkitt’s lymphoma (BL) is one of the tumours with high malignancy and rapid cell growth, derived from B-cell lymphoma. BL typically found in children at dengue-endemic and HIV-AIDS areas with low socioeconomic levels. This study was aimed to analyse the induction of apoptosis and the suppression of tumorigenesis of oral Burkitt’s lymphoma (Raji) cells using docetaxel hydrate in vitro and in vivo. Methods: In the present study, the pure experimental laboratory with post-test only control group design was carried out. Raji cell cultures were incubated with docetaxel hydrate by doses of 0, 1.25 x 10-2, 2.5 x 10-2, and 5.0 x 10-2 M; and IC50 carboplatin (3.1 x 10-6 M) as a positive control. Induction of apoptotic was analysed by double staining of acridine orange-ethidium bromide. Tumorigenesis assay was performed by inoculating Raji cells in nude mice flanks at 1 x 106 cells/mice. Tumour treatment was delivered by various doses of docetaxel hydrate peroral. Results: Apoptosis cells were significantly increased in Raji cells treated with docetaxel hydrate by doses of 2.5 x 10-2 and 5.0 x 10-2 M. The tumour volume in mice given doses of 2.5 x 10-2 and 5.0 x 10-2 M was markedly decreasing compared to control (dose of 0). Conclusion: Docetaxel hydrate has a high antitumour potency by inhibiting tumorigenesis and increasing apoptosis of Burkitt’s lymphoma cells. Keywords: Docetaxel hydrate, double staining, Burkitt’s lymphoma cell, apoptosis, tumorigenesis